2005
DOI: 10.1177/000313480507100210
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Hyperbaric Oxygen Therapy in the Management of Crush Injury and Traumatic Ischemia: An Evidence-Based Approach

Abstract: Hyperbaric oxygen therapy (HBO) has been recommended as an adjunct treatment in acute traumatic ischemia and crush injury. Several animal models have shown better outcomes when HBO is used in crush injury and compartment syndrome. Animal and in vitro models have suggested that these beneficial effects may be mediated by attenuation of ischemia-reperfusion injury. We did a systematic review of the literature using the Eastern Association for the Surgery of Trauma (EAST) recommendations for evidence-based review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…• necrotizing fasciitis 3,[8][9][10][11][12][13][14] • gas gangrene 8,9,15 • selected organ abscess 3,16 • acute traumatic peripheral ischemia 3,8 • crush injuries, especially if used early in treatment 17 • compromised skin grafts 8 • chronic refractory osteomyelitis 8,18 • delayed wound healing 3 • burns exceeding 20% of body surface 1 • radiation-induced nonhealing wounds, 19,20 osteonecrosis, 3,8,9,[21][22][23][24][25] and proctitis [26][27][28] There is some enthusiasm to use HBOT in the treatment of sports and other acute musculoskeletal injuries, but the evidence in support of efficacy is lacking. [29][30][31][32][33][34]…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…• necrotizing fasciitis 3,[8][9][10][11][12][13][14] • gas gangrene 8,9,15 • selected organ abscess 3,16 • acute traumatic peripheral ischemia 3,8 • crush injuries, especially if used early in treatment 17 • compromised skin grafts 8 • chronic refractory osteomyelitis 8,18 • delayed wound healing 3 • burns exceeding 20% of body surface 1 • radiation-induced nonhealing wounds, 19,20 osteonecrosis, 3,8,9,[21][22][23][24][25] and proctitis [26][27][28] There is some enthusiasm to use HBOT in the treatment of sports and other acute musculoskeletal injuries, but the evidence in support of efficacy is lacking. [29][30][31][32][33][34]…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Certaines études ont montré l'intérêt de l'oxygénothérapie hyperbare dans l'amélioration de l'hypoxie liée au crush syndrome [ 9 , 10 ]. La prise en charge chirurgicale du membre écrasé se fait généralement en 3 temps: stabilisation de la fracture, le plus souvent par un fixateur externe en raison des lésions cutanées et musculaires; réparation des lésions vasculaires, le plus souvent par la réalisation des pontages et enfin les aponévrotomies de décharges pour lutter contre le syndrome de loges, celui-ci est définie par une pression de loges supérieure à 30mmHg avec des signes de souffrance vasculo-nerveuses.…”
Section: Discussionunclassified
“…54 A systematic review of nine studies involving 150 patients with crush injury showed that HBOT is likely to be beneficial if administered early. 55 A larger and more rigorous RCT on open tibial fractures with severe associated soft-tissue injury will be published in the near future. 56 For compartment syndrome, no RCT has been published, but the use of HBOT is supported by animal studies and small case series.…”
Section: Acute Crush Injuries and Severe Anaemiamentioning
confidence: 99%